Mutational Spectrum Analysis of Seven Genes Associated with Thyroid Dyshormonogenesis - Xi Chen; Xiaohong Kong; Jie Zhu; Tingting Zhang; Yanwei Li; Guifeng Ding; Huijuan Wang (International Journal of Endocrinology)
Objective. Thyroid dyshormonogenesis (DH) is a genetically heterogeneous inherited disorder caused by thyroid hormone synthesis abnormalities. This study aims at comprehensively characterizing the mutation spectrum in Chinese patients with DH. Subjects and Methods. We utilized next-generation sequencing to screen for mutations in seven DH-associated genes (TPO, DUOX2, TG, DUOXA2, SLC26A4, SLC5A5, and IYD) in 21 Chinese Han patients with DH from Xinjiang Province. Results. Twenty-eight rare nonpolymorphic variants were found in 19 patients (90.5%), including 19, 5, 3, and 1 variants in DUOX2, TG, DUOXA2, and SLC26A4, respectively. Thirteen (62%) patients carried monogenic mutations, and six (28.5%) carried oligogenic mutations. Fifteen (71%) patients carried 2 or more DUOX2 (14) or DUOXA2 (1) variants. The genetic basis of DH in nine (43%) patients harboring biallelic or triallelic pathogenic variants was resolved. Seventeen patients (81%) carried DUOX2 mutations, most commonly p.R1110Q or p.K530X. No correlations were found between DUOX2 mutation types or numbers and clinical phenotypes. Conclusions. DUOX2 mutations were the most predominant genetic alterations of DH in the study cohort. Oligogenicity may explain the genetic basis of disease in many DH patients. Functional studies and further clinical studies with larger DH patient cohorts are needed to validate the roles of the mutations identified in this study.